Total versus inhaled intravenous anesthesia methods for prognosis of patients with lung, breast, or esophageal cancer: A cohort study - Che, Xiangming; Li, Tianzuo (Frontiers in Surgery, 2023)
Background: To explore the influences of total intravenous anesthesia (TIVA) and inhaled-intravenous anesthesia on the prognosis of patients with lung, breast, or esophageal cancer. Methods: In this retrospective cohort study, patients with lung, breast, or esophageal cancer who underwent surgical treatments at Beijing Shijitan Hospital between January 2010 and December 2019 were included. The patients were categorized into the TIVA group and inhaled-intravenous anesthesia group, according to the anesthesia methods used for the patients for surgery of the primary cancer. The primary outcome of this study included overall survival (OS), recurrence/metastasis. Results: Finally, 336 patients were included in this study, 119 in the TIVA group and 217 in the inhaled-intravenous anesthesia group. The OS of patients in the TIVA group was higher than in the inhaled-intravenous anesthesia group (P=0.042). There were no significant differences in the recurrence/metastasis-free survival between the two groups (P=0.296). Inhaled-intravenous anesthesia (HR=1.88, 95%CI: 1.15-3.07, P=0.012), stage III cancer (HR=5.88, 95%CI: 2.57-13.43, P<0.001), and stage IV cancer (HR=22.60, 95%CI: 8.97-56.95, P<0.001) were independently associated with recurrence/ metastasis. Comorbidities (HR=1.75, 95%CI: 1.05-2.92, P=0.033), the use of ephedrine, noradrenaline or phenylephrine during surgery (HR=2.12, 95%CI: 1.11-4.06, P=0.024), stage II cancer (HR=3.24, 95%CI: 1.08-9.68, P=0.035), stage III cancer (HR=7.60, 95%CI: 2.64-21.86, P<0.001), and stage IV cancer (HR=26.61, 95%CI: 8.57-82.64, P<0.001) were independently associated with OS. Conclusions: In patients with breast, lung, or esophageal cancer, TIVA is independently associated with a lower recurrence/metastasis rate than inhaled-intravenous anesthesia, but TIVA was not associated with OS.